Production yearbook: 1959 - Food and Agriculture Organization of the United Nations (Rome, Food and Agriculture Organization of the United Nations., 1960)
This yearbook contains the information available as of 31st December 1959 by the co-operation of Governments which have supplied most of the information in the form of replies to FAO annual questionnaires.
Includes bibliographical footnotes
hza 01/02/2019
Loans
Keywords: Agriculture; Statistics, Agricultural